In Patients Over 50 Years, Increased Age Is Associated With Decreased Odds of Documented Loss of Consciousness After a Concussion - Orlando, Alessandro; Rubin, Benjamin; Panchal, Ripul; Tanner, Allen; Hudson, John; Harken, Kyle; Madayag, Robert; Berg, Gina; Bar-Or, David (Frontiers in Neurology, 2020)
BACKGROUND: Advanced aged adults have the highest rate of traumatic brain injury (TBI) related hospital admissions, compared to younger age groups. Data were published in 2014 indicating differential injury and neurological responses to a TBI by age categories. In a recent article examining patients with mTBI and isolated subdural hematoma, it was found that older patients had a decreased risk of documented loss of consciousness (LOC). The primary objective was to determine the extent to which the odds of documented LOC changes with increasing age in a population of older adults suffering an isolated concussion and uncomplicated mTBI. METHODS: This was a retrospective study utilizing six years (2010–2015) of National Trauma Data Bank data. This study included patients with 1) diagnosis of concussion; 2) positive or negative loss of consciousness; 3) loss of consciousness durations no longer than 59 minutes or undefined; 4) age ≥50 years; 5) had a “fall” mechanism of injury; and 6) a valid emergency department Glasgow coma scale 13-15. We excluded patients 1) with any intracranial hemorrhage or intracranial injury of other and unspecified nature; 2) skull fracture; 3) an injury severity scale score >17; 4) a concussion with “unspecified” LOC (ICD-9 850.9) RESULTS: There were 7,466 patients included in the study; the median age was 70 (60–80) yrs. The risk of documented LOC was 71% (n=5,319). An 80-year-old had 72% decreased odds of having a documented LOC, compared to a 50-year-old (OR=0.28, 99.5%CI [0.23–0.34], P<.001). This association held when controlling for multiple demographic, comorbid, and clinical variables. CONCLUSION: These nationwide data suggest that in patients aged ≥50 years, a significant inverse association exists between age and odds of documented LOC after sustaining a fall-related concussion and mTBI. Additional studies are needed to validate these findings and to investigate the triad of age, documented LOC, and intracranial hemorrhage. Clinical diagnostic criteria relying on LOC might be at risk of being modified by the association between increasing age and decreasing odds of LOC.